"Social psychosis" in the development of the commodity economy - Quoc, Nguyen Anh; Y, Nguyen Van (South Eastern European Journal of Public Health, 2024)
The development of the commodity economy profoundly impacts mental phenomena, affecting how individuals perceive and respond to their social roles. In this system, the pursuit of material wealth, status, and success often becomes the driving force behind lifestyles and mental states. As individuals focus on the economy's demands, mental phenomena such as ambition, creativity, guilt, and positivity emerge, reflecting the tension between individual abilities and social expectations. The rise of self-employment and occupational diversity in the commodity economy promotes creativity and personal growth, allowing individuals to express their talents and pursue new opportunities. However, it also leads to mental challenges, including competitive anxiety, dissatisfaction, and a distorted sense of self-worth, as people attempt to fit their lives into the demands of the economic system. The shift from survival-based work to self-fulfillment through creative work has dramatically changed how individuals relate to their work. As freedom and creativity become core values, individuals experience a mix of liberation and pressure to succeed, which affects their mental health. Ultimately, mental phenomena in a commodity economy reflect the complex interplay between economic structures and individual psychology, where material success, personal identity, and social norms are constantly changing, requiring a “cure” of freedom from work, free from work pressure, for individuals to adapt, innovate, and balance their mental health in an ever-changing economic landscape.